limits x tends to infinite under root x square + x -under root x.
plss urgent ..
prakriti27:
is this ur question???
x->∞
x->∞
Answers
Answered by
6
Lim √x2 + x - √x
x->∞
let x=1/y so that y->0, when x->∞
Lim √1/y2 + 1/y - √1/y
y->0
Lim 1/y + 1/y - √1/y
y->0
Lim (1+1)/y - √1/y
y->0
Lim 2/y - √1/y
y->0
Lim 2/y - 1/√y
y->0
Lim (2√y - y)/y√y
y->0
Lim (2√y - y)/y√y x (2√y + y)/(2√y + y)
y->0
Lim (4y - y2)/y√y(2√y + y)
y->0
Lim (4y - y2)/(2y2 + y2√y)
y->0
dividing each term with the highest power of y
Lim (4y/y2 - y2/y2)/(2y2/y2 + y2√y/y2)
y->0
Lim (4/y - 1)/(2 + √y)
y->0
(4/0 - 1)/(2 + 0)
0 - 1 / 2
-1/2 it is the answer....
x->∞
let x=1/y so that y->0, when x->∞
Lim √1/y2 + 1/y - √1/y
y->0
Lim 1/y + 1/y - √1/y
y->0
Lim (1+1)/y - √1/y
y->0
Lim 2/y - √1/y
y->0
Lim 2/y - 1/√y
y->0
Lim (2√y - y)/y√y
y->0
Lim (2√y - y)/y√y x (2√y + y)/(2√y + y)
y->0
Lim (4y - y2)/y√y(2√y + y)
y->0
Lim (4y - y2)/(2y2 + y2√y)
y->0
dividing each term with the highest power of y
Lim (4y/y2 - y2/y2)/(2y2/y2 + y2√y/y2)
y->0
Lim (4/y - 1)/(2 + √y)
y->0
(4/0 - 1)/(2 + 0)
0 - 1 / 2
-1/2 it is the answer....
Answered by
2
the given question is not clearly specified.
![\lim_{x \to \infty} \sqrt{x^2+x} -\sqrt{x}\\\\= \lim_{x \to \infty}\ \ x*[\sqrt{1+\frac{1}{x}}-\frac{1}{\sqrt{x}}}]\\\\= \lim_{x \to \infty} x * [\sqrt{1+0}-0]= \lim_{x \to \infty} x\\\\=\infty \lim_{x \to \infty} \sqrt{x^2+x} -\sqrt{x}\\\\= \lim_{x \to \infty}\ \ x*[\sqrt{1+\frac{1}{x}}-\frac{1}{\sqrt{x}}}]\\\\= \lim_{x \to \infty} x * [\sqrt{1+0}-0]= \lim_{x \to \infty} x\\\\=\infty](https://tex.z-dn.net/?f=+%5Clim_%7Bx+%5Cto+%5Cinfty%7D+%5Csqrt%7Bx%5E2%2Bx%7D+-%5Csqrt%7Bx%7D%5C%5C%5C%5C%3D+%5Clim_%7Bx+%5Cto+%5Cinfty%7D%5C+%5C+x%2A%5B%5Csqrt%7B1%2B%5Cfrac%7B1%7D%7Bx%7D%7D-%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%7D%7D%7D%5D%5C%5C%5C%5C%3D+%5Clim_%7Bx+%5Cto+%5Cinfty%7D++x+%2A+%5B%5Csqrt%7B1%2B0%7D-0%5D%3D+%5Clim_%7Bx+%5Cto+%5Cinfty%7D+x%5C%5C%5C%5C%3D%5Cinfty+)
========================
![\sqrt{x^2}+x-\sqrt{x}=x+x-\sqrt{x}=2x-\sqrt{x}=x*(2-\frac{1}{\sqrt{x}})\\\\ \lim_{x \to \infty} x*(2-\frac{1}{\sqrt{x}} )\\\\=\lim_{x \to \infty} x (2-0)=\lim_{x \to \infty} x*2\\\\=\infty \sqrt{x^2}+x-\sqrt{x}=x+x-\sqrt{x}=2x-\sqrt{x}=x*(2-\frac{1}{\sqrt{x}})\\\\ \lim_{x \to \infty} x*(2-\frac{1}{\sqrt{x}} )\\\\=\lim_{x \to \infty} x (2-0)=\lim_{x \to \infty} x*2\\\\=\infty](https://tex.z-dn.net/?f=%5Csqrt%7Bx%5E2%7D%2Bx-%5Csqrt%7Bx%7D%3Dx%2Bx-%5Csqrt%7Bx%7D%3D2x-%5Csqrt%7Bx%7D%3Dx%2A%282-%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%7D%7D%29%5C%5C%5C%5C+%5Clim_%7Bx+%5Cto+%5Cinfty%7D+x%2A%282-%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%7D%7D+%29%5C%5C%5C%5C%3D%5Clim_%7Bx+%5Cto+%5Cinfty%7D+x+%282-0%29%3D%5Clim_%7Bx+%5Cto+%5Cinfty%7D+x%2A2%5C%5C%5C%5C%3D%5Cinfty)
========================
x->∞
Similar questions